2004
DOI: 10.1111/j.1365-2427.2004.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of zooplankton to nutrient enrichment and fish in shallow lakes: a pan‐European mesocosm experiment

Abstract: SUMMARY1. Responses of zooplankton to nutrient enrichment and fish predation were studied in 1998 and 1999 by carrying out parallel mesocosm experiments in six lakes across Europe. 2. Zooplankton community structure, biomass and responses to nutrient and fish manipulation showed geographical and year-to-year differences. Fish had a greater influence than nutrients in regulating zooplankton biomass and especially the relative abundances of different functional groups of zooplankton. When fish reduced the biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
64
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 52 publications
(151 reference statements)
10
64
4
1
Order By: Relevance
“…The consequences for the zooplankton community of this temporal variation in predation rate should be that medium-sized zooplankton are less affected by fish predation than larger ones, not only because of size-selective predation by adult fish but also because of a shorter period of, and less pronounced, predation from 0+ fish. This development is also commonly observed in many lakes with high 0+ fish recruitment (Post and McQueen 1987;Hansson et al 1998;Vakkilainen et al 2004). It may also be noted that after the decline in zooplankton abundances, neither medium-sized nor large zooplankton populations recovered (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The consequences for the zooplankton community of this temporal variation in predation rate should be that medium-sized zooplankton are less affected by fish predation than larger ones, not only because of size-selective predation by adult fish but also because of a shorter period of, and less pronounced, predation from 0+ fish. This development is also commonly observed in many lakes with high 0+ fish recruitment (Post and McQueen 1987;Hansson et al 1998;Vakkilainen et al 2004). It may also be noted that after the decline in zooplankton abundances, neither medium-sized nor large zooplankton populations recovered (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Alternative explanations for the association of taxon composition and the elevated P-levels are (i) a general invasion of D. galeata in this region during the 1950s and 1960s or (ii) reduced sexual reproduction of D. galeata in Lake Greifensee during the first part of the past century. A simultaneous invasion of D. galeata into both lakes seems unlikely, because D. galeata was not able to invade lakes that maintained their oligotrophic status throughout the past century (e.g., Lake Brienz) (23 (25,26). Further, large genetic differences (3 fixed loci) among the initial D. galeata invaders of both lakes reject the hypothesis of a simultaneous regional invasion.…”
Section: Discussionmentioning
confidence: 87%
“…This observation suggests that other (environmental) factors limited an earlier establishment of D. galeata in Greifensee. One of the most important factors, other than P, which alters Daphnia communities, is fish predation (26). Because predation has different impacts in shallow and deep lakes (e.g., predator control is higher in shallow lakes than in deep lakes) (30), Lake Constance and Greifensee are expected to respond differently.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies since have corroborated this hypothesis at least qualitatively (e.g. Hessen et al, 1995;Shurin, 2001;Shurin and Allen, 2001;Vakkilainen et al, 2004;Hülsmann et al, 2005) with Shurin (2001) highlighting the importance of a diverse regional species pool in determining the impact of predation on zooplankton communities. In potential agreement with this, the present study showed that proximity to other water bodies -potential sources of immigrant taxa -was linked with zooplankton species richness.…”
Section: Correlates Of Zooplankton Species Richness and Compositionmentioning
confidence: 77%